Buffering effects of soil seed banks on plant community composition in response to land use and climate. Issue 1 (23rd October 2020) - Plue, Jan; Van Calster, Hans; Auestad, Inger; Basto, Sofía; Bekker, Renée M.; Bruun, Hans Henrik; Chevalier, Richard; Decocq, Guillaume; Grandin, Ulf; Hermy, Martin; Jacquemyn, Hans; Jakobsson, Anna; et al.
Abstract: Aim: Climate and land use are key determinants of biodiversity, with past and ongoing changes posing serious threats to global ecosystems. Unlike most other organism groups, plant species can possess dormant life‐history stages such as soil seed banks, which may help plant communities to resist or at least postpone the detrimental impact of global changes. This study investigates the potential for soil seed banks to achieve this. Location: Europe. Time period: 1978–2014. Major taxa studied: Flowering plants. Methods: Using a space‐for‐time/warming approach, we study plant species richness and composition in the herb layer and the soil seed bank in 2, 796 community plots from 54 datasets in managed grasslands, forests and intermediate, successional habitats across a climate gradient. Results: Soil seed banks held more species than the herb layer, being compositionally similar across habitats. Species richness was lower in forests and successional habitats compared to grasslands, with annual temperature range more important than mean annual temperature for determining richness. Climate and land‐use effects were generally less pronounced when plant community richness included seed bank species richness, while there was no clear effect of land use and climate on compositional similarity between the seed bank and the herb layer. Main conclusions: High seed bank diversity and compositional similarity between the herb layer and seed bank plant communities may provide a potentially important functional buffer against the impact of ongoing environmental changes on plant communities. This capacity could, however, be threatened by climate warming. Dormant life‐history stages can therefore be important sources of diversity in changing environments, potentially underpinning already observed time‐lags in plant community responses to global change. However, as soil seed banks themselves appear, albeit less, vulnerable to the same changes, their potential to buffer change can only be temporary, and major community shifts may still be expected.